Enhancing Work Engagement A Case Study of The Northeastern Regional Office of The National Human Rights Commission of Thailand - Lasutham, Natpatch; Fernando, Maria Socorro; Boonchuaymetta, Ekkachai (ABAC ODI JOURNAL Vision. Action. Outcome, 2025)
Work engagement and retention are significantly influenced by a variety of intrinsic and extrinsic motivators, particularly in government organizations where salary structures and career paths are predetermined. In addition to monetary rewards, other motivations can be instrumental in inspiring employees to remain committed to the organization in the long term. This research aims to evaluate the intrinsic and extrinsic motivational factors that impact work engagement at the Northeastern Regional Office of the National Human Rights Commission of Thailand. Through a mixed-method approach grounded in the Appreciative Inquiry (AI) 4-D methodology, data were collected through individual and focus group discussions involving all 14 employees. Thematic analysis identified that meaningful work (intrinsic motivation) and a supportive work environment (extrinsic motivation) were the most important factors driving engagement. Employees found purpose in their contributions to society, while a physically and mentally supportive workplace further enhanced their dedication and motivation. Based on these insights, tailored recommendations were proposed to improve employee engagement by aligning organizational practices with these motivators.